Geothermal Distribution Analysis of Geureudong Volcano Based On Satellite Data and Fault Fracture Density (FFD) - Muhammad Isa; Zulfadhli Zulfadhli; Cut Fat Thahul; Dwiky Pobri Cesarian (Elkawnie, 2021)
Abstract: Geureudong Volcano area, Bener Meriah, has the potential to be developed as a renewable energy source. Analysis of the distribution of geothermal manifestations can be done with remote sensing techniques and direct measurement. Furthermore, information on geomorphological conditions, surface temperature, and geothermal potential distribution can be known based on the density value on the FFD (Fault Fracture Density) map and satellite image processing results. Data processing uses ArcGIS and ENVI software concerning geothermal manifestations. The analysis was performed by converting DEMNAS data to a hillshade for drawing straightness structures related to the fault. Image data processing to obtain vegetation density (NDVI), hydrological state (NDWI), and surface temperature distribution (LST). NDWI values are inversely proportional to NDVI. The LST value depends on the density of the vegetation; the higher the vegetation density, the lower the surface temperature. The FFD map is divided into three levels i.e. low (0-0.17 km/km2), moderate (0.17-0.47 km/km2) and high (0.47-1.2 km/km2). The distribution of geothermal potential is at medium and high-density levels, including the Silih Nara, Wih Pesam, and Pintu Rime Gayo areas. The straightness direction is in the north-south and southeast-northwest positions. Based on the NDVI, NDWI, and LST map analysis results, geothermal energy distribution has a rare to moderate vegetation density with surface temperatures ranging from 25.8oC-39.6oC. The result clearly shows that the Geureudong geothermal distribution is initial information before in situ exploration is carried out.Abstrak: Gunung berapi Geureudong, Bener Meriah, sangat prospektif untuk dikembangkan terutama sebagai sumber energi terbarukan. Analisis sebaran manifestasi panas bumi dapat dilakukan dengan teknik penginderaan jauh dan pengukuran langsung. Informasi geomorfologi, temperatur permukaan dan sebaran potensi panas bumi dapat diketahui berdasarkan nilai densitas pada peta FFD (Fault and Fracture Density) dan hasil pengolahan citra satelit Landsat 8. Pemrosesan data menggunakan perangkat lunak ArcGIS dan ENVI yang terkait dengan manifestasi panas bumi. Analisis dilakukan dengan mengubah data DEMNAS menjadi hillshade untuk menggambar struktur kelurusan yang berhubungan dengan sesar. Pengolahan data citra untuk mendapatkan kerapatan vegetasi (NDVI), keadaan hidrologi (NDWI) dan distribusi suhu permukaan (LST). Nilai NDWI berbanding terbalik dengan NDVI. Nilai LST tergantung pada kerapatan vegetasi, semakin tinggi kerapatan vegetasi maka semakin rendah suhu permukaan. Peta FFD dibagi menjadi tiga tingkatan; rendah (0-0,17 km/km2), sedang (0,17-0,47 km/km2) dan tinggi (0,47-1,2 km/km2). Sebaran potensi panas bumi berada pada tingkat kepadatan sedang dan tinggi, meliputi kawasan Silih Nara, Wih Pesam dan Pintu Rime Gayo. Arah kelurusan berada pada posisi utara-selatan dan tenggara-barat laut. Berdasarkan hasil analisis peta NDVI, NDWI dan LST didapatkan bahwa sebaran energi panas bumi memiliki kerapatan vegetasi jarang hingga sedang dengan temperatur permukaan berkisar antara 25.8oC-39.6oC.Hasil yang diperolehkan menunjukkan bahwa sebaran panas bumi Geureudong dengan sangat jelas tergambar sebagai informasi awal sebelum dilakukan eksplorasi lapangan (in situ).